Mycosis fungoides - primary cutaneous T-cell lymphoma - Pawlaczyk, Mariola; Filas, Violetta (Contemporary Oncology/Współczesna Onkologia, 2002)
Primary cutaneous lymphomas represent a heterogenous group of non-Hodgkin lymphomas presenting in the skin, with no evidence of extracutaneous dissemination of neoplastic process at the time of diagnosis and within 6 months after the diagnosis. Recent studies demonstrated that primary cutaneous lymphomas have very characteristic clinical and histological features, and clinical behavior and prognosis that are different from primary nodal lymphomas of the same histologic subtype, involving the skin secondarily. It resulted in the classification proposed by the European Organization for Research and Treatment of Cancer. This classification is designed specifically for the group of primary cutaneous lymphomas and is based on combination of clinical, histologic, and immunophenotypic criteria. Mycosis fungoides (MF) is the most common type of these lymphomas. The disease is characterised by monoclonal proliferation of small and medium-sized neoplastic T lymphocytes with cerebriform nuclei. Classically, MF has an indolent clinical course with slow progression over years, from patches through infiltrated plaques to tumors. Etiology of MF still remains unknown. The correct diagnosis is often difficult in the early stages because skin lesions as well as the histopathological picture can closely mimic many common benign chronic dermatoses. The combination of molecular biology techniques, immunophenotyping and histopathologic examination of skin and other tissues aids in making the early diagnosis. Early-stage disease, limited to the skin, is best treated with topical therapies such as topical nitrogen mustard, PUVA, total-skin electron beam therapy. Systemic therapy should be reserved for patients with refractory disease and patients with extracutaneous involvement.